Room temperature ionic liquids in asymmetric hetero-ene type reactions: Improving organocatalyst performance at lower temperatures - Bisogno, Fabricio Román (2021)
Room temperature ionic liquids (RTILs) have been widely used as (co)solvents in several catalytic processes modifying, in most of the cases, the catalyst activity and/or the selectivity for the studied reactions. However, there are just a few examples of their use in hydrogen bonding organocatalysis. In this paper, we show the positive effect of a set of imidazole-based ionic liquids ([bmim]BF4 and [hmim]PF6 ) in the enantioselective addition of formaldehyde tert-butylhydrazone to prochiral α-keto esters catalyzed by a sugar-based chiral thiourea. Reactions performed in the presence of low percentages of RTILs led to an increase of the catalyst activity, thereby making possible to work at lower temperatures. Thus, the chiral tert-butyl azomethyl tertiary alcohols could be obtained with moderate to good conversions and higher enantioselectivities for most of the studied substrates when using up to 30 vol% of [hmim]PF6 as a cosolvent in processes performed in toluene.